The state of food systems worldwide in the countdown to 2030 - Schneider, Kate R.; Fanzo, Jessica; Haddad, Lawrence; Herrero, Mario; Moncayo, Jose Rosero; Herforth, Anna; Remans, Roseline; Guarin, Alejandro; Resnick, Danielle; Covic, Namukolo M.; Béné, Christophe; Cattaneo, Andrea; et al. (Nature Publishing Group, 2023)
This Analysis presents a recently developed food system indicator framework and holistic monitoring architecture to track food system transformation towards global development, health and sustainability goals. Five themes are considered: (1) diets, nutrition and health; (2) environment, natural resources and production; (3) livelihoods, poverty and equity; (4) governance; and (5) resilience. Each theme is divided into three to five indicator domains, and indicators were selected to reflect each domain through a consultative process. In total, 50 indicators were selected, with at least one indicator available for every domain. Harmonized data of these 50 indicators provide a baseline assessment of the world’s food systems. We show that every country can claim positive outcomes in some parts of food systems, but none are among the highest ranked across all domains. Furthermore, some indicators are independent of national income, and each highlights a specific aspiration for healthy, sustainable and just food systems. The Food Systems Countdown Initiative will track food systems annually to 2030, amending the framework as new indicators or better data emerge.